2013
DOI: 10.1186/1471-2369-14-83
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors in adults with chronic kidney disease: characteristics of pilot participants in the Tasmanian Chronic Kidney Disease study

Abstract: BackgroundPsychosocial factors including depression, anxiety and lower social support are common in patients with chronic kidney disease (CKD). However the influence of these potentially modifiable risk factors on morbidity and mortality in this renal population is unknown. The Tasmanian Chronic Kidney Disease study is a prospective cohort study which aims to examine the influence of both biomedical and psychosocial factors on disease progression, decision making and length and quality of life in adults with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 44 publications
(45 reference statements)
2
36
0
4
Order By: Relevance
“…As this study was originally designed as a pilot to assess the feasibility of a larger cohort study, a formal power calculation was not performed. Another substantial limitation of the study design is the lack of healthy controls, dictated by the design of the Tasmanian CKD pilot study, as described in published work [39]. Results should therefore be treated as preliminary and interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this study was originally designed as a pilot to assess the feasibility of a larger cohort study, a formal power calculation was not performed. Another substantial limitation of the study design is the lack of healthy controls, dictated by the design of the Tasmanian CKD pilot study, as described in published work [39]. Results should therefore be treated as preliminary and interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for the Tasmanian Chronic Kidney Disease study has been published previously [39]. Briefly, clinical data and serum samples were obtained from 27 patients who were recruited 2 years earlier (while with CKD stage 4) via the treating physician, to participate in a prospective cohort pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…McKercher et al . () suggested that patients under dialysis lose their energy and general well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…The BDI and Beck Anxiety Inventory (BAI) are common measurements scales in studies with renal patients (Brekke et al ., ; Cukor et al ., ; Lin et al ., ; McKercher et al ., ; Turkmen et al ., ). They are both 21‐item scales that address cognitive and somatic depression or anxiety symptoms, respectively, and they are both widely used in general and clinical populations.…”
Section: Methodsmentioning
confidence: 99%